Measuring the effectiveness of gaseous virus disinfectants. Issue 6 (November 2015) - Knotzer, Simone; Kindermann, Johanna; Modrof, Jens; Kreil, Thomas R.
Abstract: The efficacy of gaseous disinfection is critical for prevention and treatment of microbial contamination in biotechnological facilities. For an evaluation of gaseous disinfection efficacy, a down-scaled laboratory model was established, using currently available carrier tests and a custom-made dry fog box. A mixture of peroxyacetic acid and hydrogen peroxide (PAA/HP) was investigated as example, at concentrations between 0.4 and 2.9 mL/m 3 for up to 3 h for inactivation of a panel of lipid-enveloped and non-lipid-enveloped viruses. The influenza viruses were most sensitive to PAA/HP treatment and minute virus of mice was most resistant. Bovine viral diarrhea virus and reovirus III showed intermediate stability and similar inactivation kinetics. Use of the dry fog box circumvents dedicating an entire lab for the investigation, which renders the generation of data more cost-effective and allows for production of highly reproducible kinetic data.